Pengaruh komunikasi Kepemimpinan terhadap Sikap Keterbukaan Anggota Komunitas Blessis di New Wine International Church: Indonesia - Takaliuang, Ria (Jurnal Ilmu Komunikasi, 2023)
The aim of this study is to determine whether there is a significant relationship between leadership communication by community leaders and the openness attitudes of Blessis community members at New Wine International Church. The research population includes all Blessis community members at New Wine International Church who are part of a WhatsApp group, totaling 160 people. A sample size of 62 individuals was determined using the Slovin formula. The method employed in this study is correlational research with a quantitative approach. Correlational quantitative research aims to identify the relationship between two or more variables within a population. The research results, through hypothesis testing, demonstrate a calculated t-value of 23.188 and a critical t-value of 2.000. It can be observed that the calculated t-value is much greater than the critical t-value. Therefore, it can be concluded that the alternative hypothesis (H_a) is accepted, and the null hypothesis (H0) is rejected. In other words, the statistical test results indicate that there is a significant influence between leadership communication and the openness attitudes of Blessis community members at New Wine International Church.